Building Motivation in Saving on Elementary School Students through Financial Literacy - Suhana, Putri Lorenza; Maryanti, Rina; Wulandary, Verra (Indonesian Journal of Multidiciplinary Research, 2022)
Financial literacy is one of the literacy skills among 6 other literacy’s that are useful in this century. Financial literacy can be used as a tool to increase the motivation of an individual in increasing his financial capacity. In terms of financial literacy, it can be tried to be applied to individuals as early as possible, here the application of understanding financial literacy is given to elementary school students so that they are expected to be able to understand the concept of money and risk in making financial decisions for the future. It is hoped that the increased financial literacy of these elementary school students can help encourage the movement to eliminate the sandwich generation chain in this generation.